Pendidikan Karakter Islami dalam Menghadapi Krisis Moral Anak di Era Media Sosial - Afriantoni Afriantoni; Aulia Putri Najiha; Lala Listira; Vinky Meylisa; Muhammad Akbar (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
This study explores the role of Islamic character education in addressing the moral crisis among children in the social media era. The rise of digital technology and globalization influences youth’s morality, causing individualistic behaviors and moral decline. The research aims to analyze the implementation of Islamic character education as a solution to this moral crisis. A qualitative method with a literature review was employed, covering publications from 2018 to 2024. The population includes journals and books related to Islamic character education, social media impact, and Islamic Religious Education curriculum. Documentation and content analysis were used as instruments, with thematic data analysis. Findings indicate that Islamic character education effectively instills faith values, digital ethics, and social responsibility, aiding in the formation of faithful and adaptive character. The conclusion emphasizes the importance of integrating moral and digital values into the curriculum and fostering collaboration within educational environments to wisely face social media challenges.